Study of the Vibrational Predissociation of the NeBr2 Complex by Computational Simulation Using the Trajectory Surface Hopping Method - Ernesto García-Alfonso; Maykel Márquez-Mijares; Jesús Rubayo-Soneira; Nadine Halberstadt; Kenneth C. Janda; Craig C. Martens (Mathematics, 2020)
The vibrational predissociation of NeBr<semantics>2</semantics> has been studied using a variety of theoretical and experimental methods, producing a large number of results. It is therefore a useful system for comparing different theoretical methods. Here, we apply the trajectory surface hopping (TSH) method that consists of propagating the dynamics of the system on a potential energy surface (PES) corresponding to quantum molecular vibrational states with possibility of hopping towards other surfaces until the van der Waals bond dissociates. This allows quantum vibrational effects to be added to a classical dynamics approach. We have also incorporated the kinetic mechanism for a better compression of the evolution of the complex. The novelty of this work is that it allows us to incorporate all the surfaces for (<semantics>v=16,17,…,29</semantics>) into the dynamics of the system. The calculated lifetimes are similar to those previously reported experimentally and theoretically. The rotational distribution, the rotational energy and j<semantics>max</semantics> are in agreement with other works, providing new information for this complex.